Pendekatan Cooperative Learning dengan Tutor Sebaya untuk Meningkatkan Aktivitas dan Prestasi Belajar Kimia Siswa MAN 1 Surakarta - Rukamtini Rukamtini (Jurnal Pendidikan Madrasah, 2017)
This research discusses the implementation of coperative learning approach conducted by the same age tutors to improve activities and achievement of students at the grade XII. The sample is taken from the students at class IA-2 of MAN I Surakarta at the first semester of academic year of 2013/2014 in the course of redox and electrochemistry. This research using classroom action research by employing two cicles, comprising the planning, actuating, observation, and reflection according to one competence standard. The research found that the implementation of coperative learning approach conducted by the same age tutors has improved activities and achievement of students at the competence standard 2, which is “implementing the concept of reductive-oxidation reaction and elecrochemistry in a technological product and daily live.” In the first cicle, student activities in learning reached 78.32% which means good/ high. This kind of activity increased into 85.81% in the second cicle that means very good/ very high. During the first cicle, the average of student grade is 72.60 with the degree of classical mastery of 52.00% which means experienced a value improvement of 12.73% and classical mastery of 44.44%. While in the second cicle, the average of student value is 78.68 that experienced an increment of 22.17% compared to before the classroom action is conducted, and it increased to 8.37% from the first cicle. The level of cassical mastery in the second cicle is 72.00%, that increased 100% compared to the level before the action and 38.46% from the first cicle. Keywords: Cooperative Learning, The Same Age Tutor, Student Activity, Learning Achievement Abstrak Penelitian ini membahas penerapan pendekatan cooperative learning dengan tutor sebaya untuk meningkatkan aktivitas dan prestasi belajar siswa kelas XII. IA-2 MAN 1 Surakarta pada semester gasal tahun pelajaran 2013/2014 dengan materi redoks dan elektrokimia. Penelitian ini adalah penelitian tindakan kelas (PTK) yang terdiri dari 2 siklus, meliputi tahap perencanaan, pelaksanaan, pengamatan dan refleksi dalam satu standar kompetensi (SK). Hasil penelitian menunjukkan bahwa penerapan pendekatan cooperative learning dengan metode tutor sebaya dapat meningkatkan aktivitas dan prestasi belajar siswa pada standar kompetensi 2, yaitu “menerapkan konsep reaksi oksidasi-reduksi dan elektrokimia dalam teknologi dan kehidupan sehari-hari”. Pada siklus 1, aktivitas siswa dalam pembelajaran 78.32% yang berarti masuk kategori baik/tinggi. Aktivitas ini meningkat menjadi 85.81% pada siklus 2 yang berarti sangat baik/sangat tinggi. Pada siklus 1, rata-rata nilai siswa 72.60 dengan tingkat ketuntasan klasikal sebesar 52.00% yang berarti terjadi perbaikan nilai sebesar 12.73% dan tingkat ketuntasan sebesar 44.44%. Pada siklus 2, rata-rata nilai siswa 78.68 yang berarti naik sebesar 22.17% dari sebelum tindakan dan naik 8.37% dari siklus 1. Tingkat ketuntasan klasikal pada siklus 2 adalah 72.00%, terjadi kenaikan sebesar 100% dari sebelum tindakan dan 38.46% dari tindakan siklus 1. Kata Kunci: Cooperative Learning, Tutor Sebaya, Aktivitas siswa, Prestasi Belajar